Effects of climate warming and precipitation change on the relationship between plant diversity and community productivity and its stability in grassland - A Wang1, 2, 2, 2, 2; LÜ Wangwang; SUN Jianping; LI Bowen; WANG Shiping (Xibei zhiwu xuebao)
[Objective] Under the background of climate warming and changing precipitation pattern, how to ensure the sustainable and stable function of grassland ecosystem and their ability to provide ecological services depends on comprehensive study of the relationship between biodiversity and productivity and its stability. This is also one of the central focus in the study of global change ecology. [Reviews] This paper systematically reviews the latest research progress in global change ecology at home and abroad, focusing on the following three aspects: First, we provide an overview of how species diversity affects productivity and its stability, as well as the potential mechanisms underlying these effects. Second, we provide a detailed overview of recent studies on the relationship between plant diversity and productivity and its stability in response to climate warming and changing precipitation, based on field experiments and other methods. Finally, we explore how dynamic changes in plant species composition play a crucial role in regulating the stability of community productivity. [Prospect] This paper puts forward some suggestions on the key issues and future research directions of plant community stability and its mechanism.